2012
DOI: 10.1111/j.1095-8649.2011.03186.x
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of the black seabream Spondyliosoma cantharus along the south‐west Portuguese coast inferred from otolith chemistry

Abstract: The chemistry of black seabream Spondyliosoma cantharus otoliths from three main fishery grounds (Olhão, Sagres and Sesimbra) located along c. 400 km of the Portuguese south and west coasts was examined. Element:Ca ratios were determined in whole otoliths and otolith cores of young adult specimens of 2-3 years of age. Using the data from whole otoliths, it was possible to discriminate among S. cantharus from the three fishing grounds with an average accuracy of 91%. Differences among fishing grounds were signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 59 publications
(61 reference statements)
1
4
0
Order By: Relevance
“…It should be high for the model ftted to be good. In the present study, the estimated coefcients of determination (R 2 ) were within the range of (0.85-1.0), which shows better predictive power and smaller dispersion of LWRs data [32,33]. Generally, variations in LWR parameters of each fsh species occur mainly due to abiotic factors such as seasons, habitats, and biological parameters like size range, sex, maturity stages, and feeding habits [34][35][36].…”
Section: Discussionsupporting
confidence: 57%
“…It should be high for the model ftted to be good. In the present study, the estimated coefcients of determination (R 2 ) were within the range of (0.85-1.0), which shows better predictive power and smaller dispersion of LWRs data [32,33]. Generally, variations in LWR parameters of each fsh species occur mainly due to abiotic factors such as seasons, habitats, and biological parameters like size range, sex, maturity stages, and feeding habits [34][35][36].…”
Section: Discussionsupporting
confidence: 57%
“…As the number of new papers increases (e.g. Correia et al 2012;Hamer et al 2012;Mercier et al 2012;Tanner et al 2012) with more data on species and areas reported with increasing detail, it should be possible to accomplish more rigorous comparisons of the patterns of elemental distributions in time and space across species. The potential for mapping otolith geochemical patterns is improving and will complement ecological studies of fish populations.…”
Section: Speciesmentioning
confidence: 99%
“…The gap between the ranges of the two species corresponds with the location of the Benguela Upwelling System (BUS), an established biographic boundary for a number of taxa (Grant & Bowen, 1998;Henriques et al, 2012Henriques et al, , 2014Henriques et al, , 2015. Throughout their respective ranges both species represent important fisheries resources and there are indications that stocks may be overfished (Correia et al, 2012).…”
Section: Introductionmentioning
confidence: 99%